Using FEM for large deformation analysis of inflated air-spring cylindrical shell made of rubber-textile cord composite - Nam, Tran Huu (Vietnam Journal of Mechanics, 2006)
An orthotropic hyperelastic constitutive model is presented for large deformation analysis of the nonlinear anisotropic hyperelastic material of the cylindrical air-spring shell used in vibroisolation of driver’s seat. Nonlinear hyperelastic constitutive equations of orthotropic composite material are incorporated into the finite strain analysis by finite element method (FEM). The results of deformation analysis of the inflated air-spring shell made of composite with rubber matrix reinforced by textile cords are given. Obtained numerical results of deformation corresponding to the experimentally measured deformation of the inflated cylindrical air-spring.